Preparation method for in-situ generation of Al3Fe nanoparticle reinforced aluminum-based composite material

Al3Fe nanoparticles are generated in situ by nanocarbon iron-packed particles and aluminum matrix, combined with ball milling and vacuum hot pressing sintering processes, the problem of nano-scale particles agglomeration is solved, and the high volume fraction uniform dispersion and mechanical properties of aluminum-based composite materials are achieved. The tensile strength and wear resistance of the material are significantly improved.

CN119265441APending Publication Date: 2025-01-07KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411392495.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In particle-reinforced aluminum-based composite materials, when the volume fraction of nano-scale particles is too high, dispersion is difficult due to agglomeration and the strength improvement is limited. The prior art has problems such as uneven dispersion of reinforcement bodies, inflexible interface reactions and component adjustments.

Method used

Al3Fe nanoparticles are generated in situ by nanocarbon iron-encapsulated particles and aluminum matrix, and high-volume fractional composite materials are prepared by ball milling and vacuum hot pressing sintering to reduce the agglomeration of the reinforcement body, and improve density and fine grains through hot extrusion change.

Benefits of technology

The high volume fraction uniform dispersion of aluminum-based composite materials is achieved, which improves the room temperature and high temperature tensile strength, hardness and wear resistance of the material, and reduces process costs and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265441A_ABST
    Figure CN119265441A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method for in-situ generation of an Al3Fe nanoparticle reinforced aluminum-based composite material, and belongs to the technical field of metal-based composite material preparation. Comprising the following steps that (1) mixed powder is prepared, and the mixed powder is weighed according to the mass percent of 3%-13% of nano carbon-coated iron powder and the balance pure Al; (2) carrying out ball-milling treatment on the mixed powder, loading the mixed powder into a ball-milling tank, and carrying out ball-milling treatment on the mixed powder in an argon environment; (3) sintering and molding; (4) carrying out hot extrusion on the sintered composite material block; the tensile strength of the high-volume-fraction in-situ generated Al3Fe nano-particle reinforced aluminum-based composite material at room temperature reaches 473.76 MPa, the hardness reaches 175.47 HV, the tensile strength at high temperature can reach 204.63 MPa, and the high-volume-fraction in-situ generated Al3Fe nano-particle reinforced aluminum-based composite material has the advantages of being high in strength, resistant to abrasion, low in thermal expansion coefficient, excellent in heat-conducting property and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an in-situ generated Al3Fe nanoparticle-reinforced aluminum-based composite material, belonging to the technical field of metal-based composite material preparation. Background Art

[0002] Aluminum-based composite materials have excellent properties such as high specific strength, high specific stiffness, high temperature resistance, corrosion resistance, and fatigue resistance. In recent years, they have been widely used in aerospace, automotive, electronics, chemical and other fields. With the development of aluminum-based composite materials, their application fields have continued to expand, especially in the aerospace and automotive fields. They have developed rapidly. Among them, particle-reinforced aluminum-based composite materials have many advantages such as light weight, good fatigue resistance and wear resistance, excellent dimensional stability, and the initial treatment of particle-reinforced aluminum-based composite materials is relatively simple, which makes it stand out among many reinforcement materials and has been explored and studied by a large number of material researchers.

[0003] In the preparation of particle-reinforced metal-based composites, research results show that for particle-reinforced aluminum-based composites, the size and volume fraction of the reinforcement particles have a significant impact on their mechanical properties; generally speaking, the smaller the particle size and the higher the volume fraction, the higher the strength of the composite material; and when the particle size is nanometer-scale and the volume fraction is too high, the agglomeration of the particles will cause the reinforcement particles to be difficult to disperse and the strength improvement will be limited; the present invention uses nanometer-scale carbon-coated iron particles and an aluminum matrix to in-situ generate Al3Fe nanoparticle-reinforced aluminum-based composites. When the volume fraction of the reinforcement is too high, the agglomeration of the iron particles is weakened due to the coating of the carbon layer, and they can be evenly dispersed in the matrix, and a dense, evenly distributed, high-volume fraction in-situ generated Al3Fe aluminum-based composite material is prepared by combining high-energy ball milling with vacuum hot pressing and sintering. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a high volume fraction in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material, which can weaken the van der Waals force between high volume fraction reinforcements, prevent the agglomeration of reinforcements, and thus increase the strength and hardness of the material; to achieve the above object, the technical solution adopted by the present invention is as follows:

[0005] A method for preparing an in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material comprises the following steps:

[0006] (1) Nano-carbon-coated iron powder and pure Al powder are ball-milled and mixed to obtain a mixed powder.

[0007] (2) Hot pressing and sintering the mixed powder.

[0008] (3) The sintered composite material block is hot extruded, and after cooling, a high volume fraction in-situ generated Al3Fe nanoparticle reinforced aluminum matrix composite material is obtained.

[0009] The mass percentage of the nano carbon-coated iron powder in the mixed powder is 3% to 13%, and the remainder is aluminum and inevitable impurities.

[0010] Preferably, the method of the present invention is to load nano carbon-coated iron powder and pure Al powder into a ball mill, and the mixed powder is ball milled under argon protection, the ball milling parameters are: ball-to-material ratio: 20:1, rotation speed 450rmp / min, ball milling time is 5 to 10 hours, and stearic acid accounting for 1% of the total mass of the mixed powder is added during the ball milling process to prevent cold welding during the ball milling process.

[0011] Preferably, the hot pressing sintering conditions in step (2) of the present invention are: keeping the temperature at 450° C. to 580° C. for 1 hour.

[0012] Preferably, in step (2) of the present invention, vacuum hot pressing sintering is performed, and the vacuum degree is <10Pa.

[0013] Preferably, the sintering pressure in step (2) of the present invention is 30-50 MPa.

[0014] Preferably, the extrusion temperature of the hot extrusion in step (3) of the present invention is 600° C., and the extrusion ratio is 9:1 to 25:1, which further improves the density of the composite material and refines the grains.

[0015] The powder preparation and powder loading work involved in all steps of the present invention are completed in a vacuum glove box to prevent oxidation of the raw materials.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] (1) The nano carbon-coated iron reinforcement particles added in the present invention have less agglomeration in the aluminum matrix and are more evenly dispersed, and the performance of the obtained aluminum-based composite material is higher than that of materials prepared by other methods.

[0018] (2) Compared with the casting method, the volume fraction of reinforcement added by powder metallurgy is not restricted, the composition can be adjusted flexibly, the risk can be reduced, and the shortcomings of grain boundary segregation and uneven distribution of the reinforcement phase can be effectively overcome. The prepared material has controllable grain refinement and uniform microstructure.

[0019] (3) By adopting the vacuum hot pressing sintering process, the sintering temperature is lower than the melting point of the composite powder. The use of a lower sintering temperature can avoid harmful interface reactions and reduce energy consumption.

[0020] (4) By adopting hot extrusion process and a higher extrusion ratio, the density of the composite material can be further improved and the grain size can be refined.

[0021] (5) The high volume fraction in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material involved in the present invention has a tensile strength of 473.76MPa and a hardness of 175.47HV at room temperature, and a tensile strength of 204.63MPa at high temperature (350°C). It has the advantages of good high temperature stability, high strength, wear resistance, low thermal expansion coefficient, and excellent thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scan of pure Al powder;

[0023] Figure 2 This is the transmission image of carbon-coated iron powder;

[0024] Figure 3 is a scanning image of the composite powder after ball milling in Example 3, Figure 3 (a) is a scan of the composite powder after ball milling at low magnification. Figure 3 (b) is a scanning image of the composite powder after ball milling at a high magnification;

[0025] Figure 4 The room temperature tensile mechanical property curves of Example 5 and Comparative Example 1;

[0026] Figure 5 is the room temperature Vickers hardness of Examples 4 and 5 and Comparative Examples 1, 3 and 4;

[0027] Figure 6 is the metallographic diagram of the materials after vacuum hot pressing sintering in Example 2 and Example 3, Figure 6 (a) is a scan of the material after vacuum hot pressing sintering in Example 2, Figure 6 (b) is a scan image of the material after vacuum hot pressing sintering in Example 3. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods, but the protection scope of the present invention is not limited to the described contents.

[0029] A method for preparing an in-situ generated Al3Fe nanoparticle-reinforced aluminum-based composite material comprises the following steps:

[0030] (1) Preparation of mixed powder: The mass percentage is 3% to 13% of nano-carbon-coated iron powder and the remainder is pure Al. Weigh the mixed powder.

[0031] (2) ball milling the mixed powder: the obtained mixed powder is placed in a ball mill, and the mixed powder is ball milled under argon protection, with ball milling parameters as follows: ball-to-material ratio: 20:1, rotation speed 450 rpm, ball milling time 5 to 10 hours, and stearic acid accounting for 1% of the total mass of the mixed powder is added during the ball milling process to prevent cold welding during the ball milling process.

[0032] (3) Sintering: The ball-milled powder is placed in a vacuum hot press furnace mold for hot pressing and sintering. The sintering pressure is 30-50 MPa, the sintering temperature is 450℃-580℃, the vacuum degree is <10Pa, and the temperature is kept for 1 hour. Pressure sintering processes such as vacuum hot pressing sintering and spark plasma sintering can be used for powder sintering. The prepared composite material can be further improved in material properties through subsequent thermal processing.

[0033] (4) The sintered composite material block is hot extruded at an extrusion temperature of 600°C and an extrusion ratio of 9:1 to 25:1, and after cooling, a high volume fraction in-situ generated Al3Fe nanoparticle reinforced aluminum matrix composite material is obtained, thereby further improving the density of the composite material.

[0034] The present invention will be further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the present invention and are not intended to limit the present invention.

[0035] Example 1

[0036] Weigh 29.1g of pure aluminum powder (such as Figure 1 As shown), 0.9g carbon-coated iron powder (as Figure 2 As shown), 0.3g stearic acid (used as a process control agent to prevent cold welding during ball milling) are placed in a stainless steel ball mill and filled with argon; a planetary ball mill is used to ball mill for 5 hours at 450rmp / min, and the ball-to-material ratio is 20:1; the mixed powder after ball milling is taken out from a vacuum glove box, and then a graphite mold is used for vacuum hot pressing sintering, the sintering temperature is 580℃, the sintering pressure is 30MPa, and the insulation time is 1h to obtain a high volume fraction in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material sample with a diameter of 30mm and a thickness of about 20mm; the surface of the sintered aluminum-based composite material is smoothed with sandpaper, and then hot extruded at 600℃ with an extrusion ratio of 25:1 to obtain a round rod-shaped aluminum material with a diameter of 6mm.

[0037] The aluminum matrix composite material was processed into a sample that can be used for stretching by wire cutting, and a tensile test was carried out to test its room temperature and high temperature tensile properties. The mechanical properties are shown in Table 1.

[0038] Example 2

[0039] 28.5g pure aluminum powder, 1.5g carbon-coated iron powder, and 0.3g stearic acid (used as a process control agent to prevent cold welding during ball milling) were weighed and placed in a stainless steel ball mill, and filled with argon; a planetary ball mill was used to ball mill at 450rmp / min for 8 hours, with a ball-to-material ratio of 20:1; then a graphite mold was used for vacuum hot pressing sintering, the sintering temperature was 500℃, the sintering pressure was 50MPa, and the insulation time was 1h, to obtain a high volume fraction in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material sample with a diameter of 30mm and a thickness of about 20mm; the surface of the sintered aluminum-based composite material was smoothed with sandpaper, and then hot extruded at 600℃ with an extrusion ratio of 25:1 to obtain a round rod-shaped aluminum material with a diameter of 6mm.

[0040] The aluminum matrix composite material was processed into a sample that can be used for stretching by wire cutting, and a tensile test was carried out to test its room temperature and high temperature tensile properties. The mechanical properties are shown in Table 1.

[0041] Example 3

[0042] 27.6g pure aluminum powder, 2.4g carbon-coated iron powder, and 0.3g stearic acid (used as a process control agent to prevent cold welding during ball milling) were weighed and placed in a stainless steel ball mill, and filled with argon; a planetary ball mill was used to ball mill for 10 hours at 450rmp / min, with a ball-to-material ratio of 20:1; then a graphite mold was used for vacuum hot pressing sintering, the sintering temperature was 550°C, the sintering pressure was 40MPa, and the insulation time was 1h, to obtain a high volume fraction in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material sample with a diameter of 30mm and a thickness of about 20mm; the surface of the sintered aluminum-based composite material was smoothed with sandpaper, and then hot extruded at 600°C with an extrusion ratio of 9:1 to obtain a round rod-shaped aluminum material with a diameter of 10mm.

[0043] The aluminum matrix composite material was processed into a sample that can be used for stretching by wire cutting, and a tensile test was carried out to test its room temperature and high temperature tensile properties. The mechanical properties are shown in Table 1.

[0044] Example 4

[0045] 27g pure aluminum powder, 3g carbon-coated iron powder, and 0.3g stearic acid (used as a process control agent to prevent cold welding during ball milling) were weighed and placed in a stainless steel ball mill, and filled with argon; a planetary ball mill was used to ball mill for 10 hours at 450rmp / min, with a ball-to-material ratio of 20:1; then a graphite mold was used for vacuum hot pressing sintering, the sintering temperature was 450°C, the sintering pressure was 50MPa, and the insulation time was 1h, to obtain a high volume fraction in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material sample with a diameter of 30mm and a thickness of about 20mm; the surface of the sintered aluminum-based composite material was smoothed with sandpaper, and then hot extruded at 600°C with an extrusion ratio of 14:1 to obtain a round rod-shaped aluminum material with a diameter of 8mm.

[0046] The aluminum matrix composite material was processed into a sample that can be used for stretching by wire cutting, and a tensile test was carried out to test its room temperature and high temperature tensile properties. The mechanical properties are shown in Table 1.

[0047] Example 5

[0048] 26.1g pure aluminum powder, 3.9g carbon-coated iron powder, and 0.3g stearic acid (used as a process control agent to prevent cold welding during ball milling) were weighed and placed in a stainless steel ball mill, and filled with argon; a planetary ball mill was used to ball mill for 10 hours at 450rmp / min, with a ball-to-material ratio of 20:1; then a graphite mold was used for vacuum hot pressing sintering, the sintering temperature was 580°C, the sintering pressure was 50MPa, and the insulation time was 1h, to obtain a high volume fraction in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material sample with a diameter of 30mm and a thickness of about 20mm; the surface of the sintered aluminum-based composite material was smoothed with sandpaper, and then hot extruded at 600°C with an extrusion ratio of 25:1 to obtain a round rod-shaped aluminum material with a diameter of 6mm.

[0049] The aluminum matrix composite material is processed into a sample that can be stretched by wire cutting, and a tensile test is carried out to test its room temperature and high temperature tensile properties. The tensile engineering stress-strain curve of the composite material is as follows: Figure 4 The mechanical properties are shown in Table 1.

[0050] Comparative Example 1

[0051] For comparison, the difference between this comparative example and Example 1 is that no nano Fe@C particle reinforcement is added, and the same ball milling, sintering and extrusion process as Example 5 is adopted.

[0052] 30g pure aluminum powder and 0.3g stearic acid (used as a process control agent to prevent cold welding during ball milling) were weighed and placed in a stainless steel ball mill, and filled with argon; a planetary ball mill was used to ball mill for 10 hours at 450rmp / min, with a ball-to-material ratio of 20:1; the mixed powder after ball milling was taken out from a vacuum glove box, and then vacuum hot pressing sintering was performed using a graphite mold, the sintering temperature was 580°C, the sintering pressure was 50MPa, and the insulation time was 1h to obtain a high volume fraction in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material sample with a diameter of 30mm and a thickness of about 20mm; the surface of the sintered aluminum-based composite material was smoothed with sandpaper, and then hot extruded at 600°C with an extrusion ratio of 25:1 to obtain a round rod-shaped aluminum material with a diameter of 6mm.

[0053] The aluminum matrix composite material was processed into a sample that can be used for stretching by wire cutting, and a tensile test was carried out to test its room temperature and high temperature tensile properties. The mechanical properties are shown in Table 1.

[0054] Comparative Example 2

[0055] As a comparison, the difference between this comparative example and Example 5 is that the ball milling time is shortened, and the high-speed ball milling is performed for 4 hours.

[0056] 26.1g pure aluminum powder, 3.9g carbon-coated iron powder, and 0.3g stearic acid (used as a process control agent to prevent cold welding during ball milling) were weighed and placed in a stainless steel ball mill, and filled with argon; a planetary ball mill was used for ball milling at 450rmp / min for 4 hours, with a ball-to-material ratio of 20:1; the mixed powder after ball milling was taken out from a vacuum glove box, and then vacuum hot-pressed sintering was performed using a graphite mold, the sintering temperature was 580°C, the sintering pressure was 50MPa, and the insulation time was 1h, to obtain a high volume fraction in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material sample with a diameter of 30mm and a thickness of about 20mm; the surface of the sintered aluminum-based composite material was smoothed with sandpaper, and then hot extruded at 600°C with an extrusion ratio of 25:1 to obtain a round rod-shaped aluminum material with a diameter of 6mm.

[0057] The aluminum matrix composite material was processed into a sample that can be used for stretching by wire cutting, and a tensile test was carried out to test its room temperature and high temperature tensile properties. The mechanical properties are shown in Table 1.

[0058] Comparative Example 3

[0059] As a comparison, the difference between this comparative example and Example 5 is that the sintering pressure is reduced, and the vacuum hot pressing sintering is performed at a sintering pressure of 25 MPa.

[0060] 26.1g pure aluminum powder, 3.9g carbon-coated iron powder, and 0.3g stearic acid (used as a process control agent to prevent cold welding during ball milling) were weighed and placed in a stainless steel ball mill, and filled with argon; a planetary ball mill was used for ball milling at 450rmp / min for 10 hours, with a ball-to-material ratio of 20:1; the mixed powder after ball milling was taken out from a vacuum glove box, and then vacuum hot-pressed sintering was performed using a graphite mold, the sintering temperature was 580°C, the sintering pressure was 25MPa, and the insulation time was 1h, to obtain a high volume fraction in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material sample with a diameter of 30mm and a thickness of about 20mm; the surface of the sintered aluminum-based composite material was smoothed with sandpaper, and then hot extruded at 600°C with an extrusion ratio of 25:1 to obtain a round rod-shaped aluminum material with a diameter of 6mm.

[0061] The aluminum matrix composite material was processed into a sample that can be used for stretching by wire cutting, and a tensile test was carried out to test its room temperature and high temperature tensile properties. The mechanical properties are shown in Table 1.

[0062] Comparative Example 4

[0063] As a comparison, the difference between this comparative example and Example 5 is that the extrusion ratio is reduced, and the sintered block is hot extruded with an extrusion ratio of 6:1.

[0064] 26.1g pure aluminum powder, 3.9g carbon-coated iron powder, and 0.3g stearic acid (used as a process control agent to prevent cold welding during ball milling) were weighed and placed in a stainless steel ball mill, and filled with argon; a planetary ball mill was used for ball milling at 450rmp / min for 10 hours, with a ball-to-material ratio of 20:1; the mixed powder after ball milling was taken out from a vacuum glove box, and then a graphite mold was vacuum hot-pressed and sintered at a sintering temperature of 580°C, a sintering pressure of 50MPa, and a holding time of 1h to obtain a high volume fraction in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material sample with a diameter of 30mm and a thickness of about 20mm; the surface of the sintered aluminum-based composite material was smoothed with sandpaper, and then hot extruded at 600°C with an extrusion ratio of 6:1 to obtain a round rod-shaped aluminum material with a diameter of 12mm.

[0065] The aluminum matrix composite material was processed into a sample that can be used for stretching by wire cutting, and a tensile test was carried out to test its room temperature and high temperature tensile properties. The mechanical properties are shown in Table 1.

[0066] Table 1

[0067]

[0068] It can be seen from Table 1 that by comparing Example 1 with Examples 1-5, it can be seen that with the increase in the mass fraction of added nano-carbon-coated iron particles, the van der Waals force between the nano-iron particles is weakened due to the coating of the carbon layer, and the nano-iron particles with a high volume fraction are easily evenly distributed in the aluminum matrix, hindering the movement of dislocations. Therefore, the room temperature and high temperature tensile strength of the composite material gradually increases, showing a good law between the composition and the mechanical properties, which is convenient for further regulation of the mechanical properties of the organization.

[0069] By comparing Example 1 with Comparative Example 1, it can be seen that the nano Al3Fe particles are generated in situ by adding nano-carbon-coated iron and the aluminum matrix, which has the advantages of good compatibility with the matrix, clean interface, firm bonding, and inhibition of crack propagation, and can further improve the room temperature and high temperature tensile strength of the composite material.

[0070] By comparing Example 5 with Comparative Examples 2-4, with the increase of ball milling time, sintering pressure and extrusion ratio, nano Al3Fe particles gradually enter the Al particles and are evenly dispersed, and the grain size of the aluminum matrix is ​​continuously refined, the particles are more evenly dispersed, the interface bonding is better, and the reinforcement efficiency is higher, which can significantly improve the mechanical properties of the composite materials at room temperature and high temperature.

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing an in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material, characterized in that: The specific steps include: (1) ball-milling nano-carbon-coated iron powder and pure Al powder to obtain a mixed powder; (2) hot pressing and sintering the mixed powder; (3) The sintered composite material block is hot extruded, and after cooling, a high volume fraction in-situ generated Al3Fe nanoparticle reinforced aluminum matrix composite material is obtained.

2. The method for preparing the in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material according to claim 1, characterized in that: The mass percentage of nano carbon-coated iron powder in the mixed powder is 3% to 13%.

3. The method for preparing the in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material according to claim 1, characterized in that: Nano carbon-coated iron powder and pure Al powder are loaded into a ball mill, and the mixed powder is ball milled under argon protection. The ball milling parameters are: ball-to-material ratio: 20:1, rotation speed 450 rpm, ball milling time 5 to 10 hours, and stearic acid accounting for 1% of the total mass of the mixed powder is added during the ball milling process.

4. The method for preparing the in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material according to claim 1, characterized in that: The hot pressing sintering conditions in step (2) are: 450°C to 580°C and kept warm for 1 hour.

5. The method for preparing the in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material according to claim 4, characterized in that: In step (2), vacuum hot pressing is used for sintering, and the vacuum degree is <10Pa.

6. The method for preparing the in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material according to claim 5, characterized in that: The sintering pressure in step (2) is 30-50 MPa.

7. The method for preparing the in-situ generated Al3Fe nanoparticle reinforced aluminum-based composite material according to claim 1, characterized in that: The extrusion temperature of the hot extrusion in step (3) is 600° C., and the extrusion ratio is 9:1 to 25:1.

Citation Information

Cited By

  • Preparation method of nano TiC particle reinforced aluminum-based composite material

    CN120425187A